Islamic Boarding Schools and Renewal, Directions and Implications - Setiawan, Andi; Majid, Abdul; Warisno, Andi; Andari, An An; Anshori, M Afif (Graduate Program Magister Manajemen Pendidikan, 2023)
The goal of this paper is to look at the Future of Islamic Boarding Schools and their Implications. This study employs a qualitative descriptive approach in conjunction with library research, by collecting books and other sources related to research objects. The findings discussed in this paper, along with their implications for Islamic boarding school and renewal. The Islamic boarding school education system comes first. Second, consider the Islamic boarding school’s reaction to reforms. Third, there was a fight in the Islamic boarding school. Fourth, consider the scope and implications of Islamic boarding school renewal.